Evaluation of last-year dental students' skill at the Tabriz Faculty of Dentistry about principles of writing prescriptions - Javad Yazdani; Mehran Kooshki; Maryam Pourkazemi; Ensiyeh Maljaei; Milad Ghanizadeh (Tabriz University of Medical Sciences, 2018)
Background: Inattention to the principles of writing prescriptions might give rise to ineffective or hazardous treatment and inflict injuries to the patient. The aim of this study was to evaluate the last-year dental students' skill in writing prescription at the Tabriz Faculty of Dentistry in 2016-2017. Methods: In this cross-sectional study, all last-year dental students (92 students) at the Tabriz Faculty of Dentistry were asked to write separate prescription for 3 patients. The level of compliance with the principles of writing prescriptions was evaluated based on the WHO checklist, which consists of the following items: patient's name, gender and age; date of prescription; Rx symbol; the form and name of the drug; the dose of the medication; the number of the drugs to be filled; administration interval; the strength of the drug; route of administration; the signature and seal of the physician; and the refill order. Each correct item was given a positive score and each incorrect item received no score (score range: 0-45). Results: 10.9%, 43.5% and 45.6% of the students exhibited high, moderate and low skill. The mean score was 27.75 (SD 8.75) of a total possible score of 45. There were no significant differences between male and female students (P = 0.7, CI = -4.5 to 3.2, effect size = -0.035). Conclusion: Overall, final-year dental students' skill in writing prescriptions was at a moderate level and no student fully observed all the principles for the correct method of writing prescriptions.